Eye Tracking Research On Learning Difficulties For Children With Hearing Impairments - Y.K. Smirnova (Moscow State University of Psychology and Education, 2023)
The article analyzes the specifics of the organization of the perceptual activity of preschoolers with and without hearing impairment with different forms of instruction in the learning process. A comparative study of a sample of children aged 4-6 years was carried out: typically developing and with sensorineural hearing loss after cochlear implantation. During the experiment, the combinations of verbal and non-verbal instructions were varied. During the training task, eye movements were recorded by a Pupil Labs mobile tracker in the form of glasses. When changing the forms of instructions in 4 series of the experiment, it was found that a measure of reducing visual attention in the learning process in children with hearing impairment is changes in the periods of fixations when they are focused on the regions targeted for the learning task (such as a form for completing the task, a sample, an adult's face) . In children with hearing impairment, during the learning process, a transformation of perceptual processes was recorded depending on the form of the instruction: whether fixation on non-target stimuli decreases, fixation occurs faster or slower, whether the cognitive complexity of information decreases, whether fixation will be longer in target areas, whether there is constant attention and shared attention with an adult. It is shown how a different form of instruction allows you to restructure the perception of a child with hearing impairment, focusing attention on the elements relevant to the task. Differences in the change in the perceptual activity of typically developing preschoolers and preschoolers with hearing impairment were analyzed with different forms of instruction. It was found that the movement of the eyes of children with hearing impairment, unlike their peers, can be characterized by a significant reduction in orienting perceptual actions. The most effective for children with hearing impairment is the simultaneous use of multimodal means of explaining instructions or separately non-verbal forms of instructions (showing an action or a sample). For typically developing children, non-verbal forms of instruction without verbal accompaniment are not as effective.